Enhancing the efficiency of the offensive attack for experienced volleyball players, considering their physical balance metrics - Lutkova N.V. ,; Makarov Yu.M. ,; Zarodnyuk G.V. ,; Alekseeva N.D., (Theory and Practice of Physical Culture, 2025)
Objective of the study was to increase the effectiveness of an offensive strike among skilled volleyball players, it is important to take into account the body's balance. Methods and structure of the study. The evaluation of volleyball activities was conducted within the framework of the St. Petersburg Championship for men's teams in the 2022-2023 season. A customized version of the Data Volley software was employed to monitor the progress of competitive performances. To pinpoint a single technical and tactical action, the video camera was positioned behind the front line of the court, and the effectiveness of the offensive strike was assessed in accordance with the classification outlined in the manual for this software. A total of 32 matches between the two teams were analyzed. The study aimed to assess the readiness of the players to execute an offensive strike. The analysis of body balance indicators was conducted using the ST-150 stability platform. The experiment involved exercises designed to strengthen the muscles responsible for maintaining body balance. The study involved 24 volleyball players, representing the SSHOR Ekran and Peterburgaz teams. Results and conclusions. 1. It has been confirmed that the initial indicators of physical equilibrium and balance control in volleyball teams are consistent. 2. The appropriateness of incorporating exercises to enhance the muscles responsible for maintaining physical equilibrium has been established in three distinct areas: strengthening the musculoskeletal system of the ankle joint, strengthening the muscles of the back and spine, and developing jumping ability and managing physical equilibrium. 3. It has been observed that the improvement in jumping performance is closely linked to the development of physical equilibrium and balance control in volleyball players. 4. It has been determined that the players in the experimental group significantly improved their performance in executing offensive strikes during competitive matches.